Cytogenetic and cytological analysis of Colombian cape gooseberry genetic material for breeding purposes - Florez, Viviana; Liberato Guio, Sara Alejandra; Sanchez Betancourt, Erika; Garcia Arias, Francy Liliana; Nuñez Zarantes, Victor Manuel (Published by Firenze University Press, 2024)
The cape gooseberry, Physalis peruviana L., is a crop that is transitioning from a semi-wild rural food source to becoming an international export commodity fruit deserving of greater attention from the scientific community, producers, policy makers, and opinion makers. Despite its importance, the crop has serious technological development challenges, mainly associated with the limited supply of genetically improved materials for producers and consumers. To bridge this gap, the present study determined the level of ploidy of 100 genotypes of cape gooseberry from a working collection by counting the number of chromosomes and chloroplasts, to include them in the breeding program. The number of chromosomes in dividing cells of root-tip meristems, as well as the number of chloroplasts per guard cell, from plants grown under in vitro and ex vitro conditions were determined. Haploid with 24 chromosomes, doubled haploid, tetraploid with 48 chromosomes, aneuploid (44 and 49 chromosomes), and mixoploid genotypes with 36 to 86 chromosomes were found. The number of chloroplasts per guard cell ranged from 4-8, 6-16, 7-16 and 9-21 for the haploid, aneuploid, doubled haploid-tetraploid, and mixoploid genotypes, respectively. The results showed evidence of a high cytogenetic diversity in the evaluated genotypes.